Respostas

2013-11-27T11:56:30-02:00
3) 
(-12):(+2).(-2-2-5) = 
(-6).(-9) = 54

2)
(-10):(-2)-(-1).(-3).(+3)=
5 - (+3) = 
5 - 3 = 2

1)
-9 + 15:(-3) - (-2).7 = 
-9 - 5 - (-14) = 
-9 -5 + 14 = 
-14 + 14 = 0
 

As alternativas 2 e 3 estão erradas.
2013-11-27T12:43:36-02:00
1. O valor da expressão   - 9 + 15 : (- 3) - (- 2) . 7 é:
- 9 + 15 ÷ (- 3) + 2 * 7 =
- 9 - 5 + 14 =
- 14 + 14 =
0

2. O valor da expressão  (- 10) : (- 2) - (- 1) . (- 3) . (+ 3) é:
(- 10) 
÷ (- 2) + 1 * (- 3) * 3 =
5 - 3 * 3 =
5 - 9 =
- 4

3. O valor da expressão (- 12) : (+ 2) . (- 2 - 3 - 5) é:
- 6 * (- 2 - 3 - 5) =
- 6 * (- 10) =
60